Drought: We know what to do, why don't we do it? - Roba, Guyo Malicha (New Humanitarian, 2022)
The 20 million people struggling to survive a scorching drought in the Horn of Africa are victims not only of a climate crisis but of the failings of governments and humanitarians to heed the lessons from earlier disasters.